DAMPAK REALISASI PENGELUARAN PROVINSI TERHADAP PENDAPATAN DAERAH PROVINSI PAPUA - Rienette Marlissa, Elsyan (Indonesian Journal of Socio Economics)
The objective of this research is (1) to measure and evaluate proportion of realization of provincial expenditure in Papuaâs provincial budget (APBD) of 2001â2005, and (2) to examine the impact of provincial expenditure to provincial income of 2001â2005. This study use 2001â2005 provincial budget and is analyzed using multiple regression analysis followed by F test and CBS (Comparative Budget Statement). The study suggests that (1) APBD of Papua Province has not been allocated proportionately.Â  Budget allocation did not comply with line-item budgetary system resulting disproportional allocation. (2) simultaneous and partial analysis show that provincial expenditure has influenced significantly to the Income of Papua Province. Â Simultaneous regression analysis suggests that provincial expenditure affects targeted of provincial income.Â  Partial analysis also suggests that all variables significantly affects target of provincial expenditures.